From Beyond the Grave: The Affective Power of James VII and II's Relics - Anna Groundwater (Royal Studies Journal, 2025)
Stimulated by the recent acquisition by National Museums Scotland of a silver locket said to contain the pericardium of James VII and II’s heart, this paper considers the part played by such relics and their containers, the reliquaries, in supporting the Stuart challenge to Hanoverian rule, and the connections they facilitated between loyal Jacobites and their absent monarchs, whether alive or dead. On the death of the exiled James in France, in 1701, his body was eviscerated, and these remains divided between five ecclesiastical institutions. The distribution, loss and reappearance of some of these relics helped to promote a message of the virtuous piety of the exiled king, and through him, the sanctity of the Stuart dynasty and its claim to the Scottish, English and Irish crowns. They were intended to advertise the righteousness of the Jacobite cause and secure support. Arguably in death, James’s reach was extended from beyond the grave, extending geographically in location, and temporally down through the succeeding generations of relic custodians.